Ethical Policy and The Emergence Of Indonesian Nationalism 1908-1919 in The High School History Textbooks For Grade XI - Sudarmaji, Arif Krisna; Abidin, Rahman (HISTORIKA, 2019)
This study aims to analyze the implementation of the values of nationalism in Indonesian History textbooks in class XI. Issues raised include: (1). How nationalism can emerge in Indonesia. (2). How the influence of nationalism itself for the Indonesian people. The research method used is critical discourses analysis, which is analyzing discourse contained in Indonesian History textbooks. The approach used is the theory of nationalism E.J. Hobsbawm. Nationalism develops through three phases, ethnolinguistic nationalism, xenophobia, passionate ethnocentrism. The results of the study show that nationalism emerged as a response to Dutch colonialism and imperialism. Emerging local elites were enlightened as a result of the ethical politics of the early 20th century. Many movement organizations were formed, including the Indische Partij, which provided the essential foundation for Indonesian ideas as inspiration for the emergence of the conception of the awareness of modern Indonesian nationhood in 1928.